APPLICATION OF SCADA SYSTEM IN AUTOMATION OF WASTEWATER TREATMENT PROCESSES - Salohiddinov Fayzulloh Fazliddin o’g’li; Saidahmedov Omadbek Soibjon o’g’li (European Science Publishing, 2024)
Supervisory Control and Data Acquisition (SCADA) systems play a crucial role in the efficient operation and management of wastewater treatment facilities. These systems integrate various technologies to monitor, control, and optimize the complex processes involved in treating wastewater. Here's an overview of the SCADA system in wastewater treatment:
Keywords: SCADA systems, wastewater treatment plant, PLC, HMI, software, hardware, license, screens, automation, communication network.